KINERJA ABU BATU BARA BERCAMPUR KAYU PADA STABILITAS DAN RONGGA PORI ASPAL HOT MIX HRS - WC - Muhammad Shalahuddin (Jurnal APTEK, 2010)
The filler is difficult to get it in nature, hence to get it always use filler from fine aggregate and medium aggregate, cement and lime. Minus filler in HRS-WC caused bleeding. Filler characteristic have much space surface in unit and can absorbed asphalt bitumen and decrease void. Fly ash is the fine particulate matter (filler) which is prepitated from the stack of pulverized coal-wood fired boiler at electrical power generating plants PT. RAPP. The primary benefits of using fly ash are (1) environmental incentives becaused material used does not have to be wasted (2) cost saving, becaused fly ash is typically cheaper than cement and lime, and (3) availability, because fly ash sources are distributed geographically across the state.HRS-WC is a high durability HMA, it have more than asphalt bitumen and filler. Asphalt bitumen increase bitumen film thickness and filler increase void. Research activities are underway to investigate more effective and efficient ways of adding fly ash at the HMA production site. This research with 60 total sample specimen of HMA, variation of fly ash are 0 %, 6 % ; 10 % and 12 % and variation of bitumen are 5 %, 5,5 %, 6 %, 6,5 % and 7 %.